Re-examining the reliability and validity of 30-15IFT for VO2max prediction in male collegiate soccer players: a pilot study - Cheng, Ruiqi; Lin, Weian; Song, Lin; Pan, Jinchen; Wang, Ning; Li, Xiaotian (Frontiers in Physiology, 2025)
PurposeThis pilot study aimed to determine the reliability and validity of the 30-15 Intermittent Fitness Test (30-15IFT) in male collegiate soccer players. A secondary aim was to develop a new, population-specific equation for predicting maximal oxygen uptake (VO2max) and to compare its predictive validity against a widely used general equation.MethodsTwenty well-trained male collegiate soccer players (age 19.5 ± 1.3 years, height 177.8 ± 6.3 cm, body mass 68.0 ± 14.3 kg; training experience 10.8 ± 3.0 years) participated in this study, and goalkeepers and players with injuries were excluded. A repeated-measures design was utilized. The participants completed three testing sessions separated by 1-week intervals: one trial of a continuous treadmill running test (CT) with running speed increasing by 1 km/h every minute to assess the validity of the 30-15IFT and two trials of the 30-15IFT to evaluate reliability. The 30-15IFT involves 30-s runs across a 40-m course interspersed with 15 s of walking, with running speed increasing by 0.5 km/h every 45-s stage. Maximal intermittent running velocity (VIFT), maximum heart rate (HRmax), and maximal oxygen consumption (VO2max) were collected for both tests. Reliability was assessed using the intraclass correlation coefficient (ICC) and typical error (TE). Validity was evaluated via Pearson correlation and Bland-Altman analysis. A multiple linear regression model was developed and cross-validated, with its predictive accuracy and agreement directly compared to those of the equation.ResultsThe 30-15IFT demonstrated high reliability for all key metrics (ICC = 0.81–0.92, CV = 1.43–1.69%). Despite large correlations with CT measures (r = 0.62–0.77), Bland-Altman analysis revealed significant systematic bias and wide limits of agreement. The newly developed population-specific equation (r = 0.72, SEE = 2.90 mL/kg/min) demonstrated substantially lower bias (SEE = 2.90 mL/kg/min) compared to the general equation when applied to this cohort (SEE = 4.91 mL/kg/min).ConclusionThis pilot study demonstrates that the 30-15IFT is a reliable tool for monitoring sport-specific performance, but should not be used interchangeably with laboratory-based tests due to significant disagreement. The application of general prediction equations can lead to considerable error. Future research should therefore focus on developing and validating these prediction models in larger, more diverse populations to improve their predictive accuracy and generalizability.